From goals to data and back again : adding backbone to developmental intervention for children with autism - Lehman, Jill Fain (Jessica Kingsley Publishers, 2003)
Early intervention is now accepted as essential in helping children with Autism Spectrum Disorders (ASDs) to cope with the future demands of daily living, education and long-term independence. Choosing the most suitable intervention strategy is difficult because there are a large number of theories, including TEACCH, Floor-time and ABA, and each child with autism presents differently. In this book, the authors argue that theory must be combined with data in order for it to be used effectively in developmental intervention. Aimed at professionals, as well as parents who want to be more involved.